Tuning the Anode–Electrolyte Interface Chemistry for Garnet‐Based Solid‐State Li Metal Batteries - Deng, Tao; Ji, Xiao; Zhao, Yang; Cao, Longsheng; Li, Shuang; Hwang, Sooyeon; Luo, Chao; Wang, Pengfei; Jia, Haiping; Fan, Xiulin; Lu, Xiaochuan; Su, Dong; et al. (Advanced materials (Weinheim), 2020)
Lithium (Li) metal is a promising candidate as the anode for high‐energy‐density solid‐state batteries. However, interface issues, including large interfacial resistance and the generation of Li dendrites, have always frustrated the attempt to commercialize solid‐state Li metal batteries (SSLBs). Here, it is reported that infusing garnet‐type solid electrolytes (GSEs) with the air‐stable electrolyte Li3PO4 (LPO) dramatically reduces the interfacial resistance to ≈1 Ω cm2 and achieves a high critical current density of 2.2 mA cm−2 under ambient conditions due to the enhanced interfacial stability to the Li metal anode. The coated and infused LPO electrolytes not only improve the mechanical strength and Li‐ion conductivity of the grain boundaries, but also form a stable Li‐ion conductive but electron‐insulating LPO‐derived solid‐electrolyte interphase between the Li metal and the GSE. Consequently, the growth of Li dendrites is eliminated and the direct reduction of the GSE by Li metal over a long cycle life is prevented. This interface engineering approach together with grain‐boundary modification on GSEs represents a promising strategy to revolutionize the anode–electrolyte interface chemistry for SSLBs and provides a new design strategy for other types of solid‐state batteries. Li3PO4‐infused Li6.5La3Zr1.5Ta0.5O12 via atomic layer deposition with simple annealing is demonstrated to have excellent moisture stability and interfacial stability to a lithium anode by presenting negligible interfacial resistance (≈1 Ω cm2) and a record‐high critical current density of 2.2 mA cm−2 at ambient conditions. This new surface/subsurface engineering approach stabilizes the anode–electrolyte interface for solid‐state batteries.